Scopoletin, a coumarin derivative compound isolated from Macaranga gigantifolia Merr - Akhmad Darmawan , , Soleh Kosela, Leonardus B.S. Kardono, and Yana M. Syah (Journal of Applied Pharmaceutical Science)
Scopoletin (1), a coumarin derivative compound has been isolated from methanol extract of Macaranga gigantifolia Merr. leaves using chromatography methods. Chemical structure determination carried out based on spectroscopic data and compared with a reference. Scopoletin cytotoxicity test using MTT assay method against P-388 murine leukemia cells showed strong cytotoxic activity with IC50 17.42 μg/mL.
Keywords: Scopoletin, Coumarin Derivative, Macaranga Gigantifolia Merr.